Agility testing in top-level professional basketballplayers - Moreno, D.; Peña, X.; Buscà, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: In the last years, agility has become an important topic in team sports testing being included within the training contents and assessment procedures of the main professional leagues, such as the NBA and the NFL. Regarding to basketball, many studies have currently approached the relationship between agility and physical performance using several tests (Jackovlevic et al. 2012), while trying, at the same time, to explore the different characteristics of playing positions (Scalan et al., 2013). Our purpose was to investigate those position-related differences in top-level professional players. Methods: Thirty-nine male adult subjects participated in the study during the last four years and were tested at least twice a year. After performing a specific warm-up, players completed two tests, a 2x10m test and a 4x5m test, using two Velleman PME10D® photocell gates connected to a Chronojump® software that provided speed outcomes. Comparisons were made considering three specific game positions (`G`: guards, `F`: forwards and `C`: centers). Results: Both tests showed a moderate, but significant, correlation (r = 0,589; p<0,001). Forwards showed best performances in the 2x10 test when compared to the rest of the groups (p = 0,001), and in the 4x5 test when compared to guards (p = 0,001). Discussion: Agility measurements are commonly based in closed-skill tests, such as the 4x5m or the 2x10m (Scanlan et al. 2013). The findings of the current study are consistent with those of Jackovljevic et al. (2012), suggesting that results from both tests seem to be closely related. At the same time, the observed correlations lead us to believe that there is a close relationship between speed and agility explaining the 2x10 m test results (Sekulic et al., 2013). Comparisons among roles revealed that forwards have better ability to accelerate, decelerate and to change directions than any other position in the game.